Improving care for SUD patients with complex trauma–relationships between childhood trauma, dissociation, and suicidal behavior in female patients with PTSD and SUD - Gidzgier, Piotr A.; Bari, Melav; López-Atanes, Mayte; Lotzin, Annett; Grundmann, Johanna; Hiller, Philipp; Schneider, Barbara; Schäfer, Ingo (Frontiers in Psychiatry, 2023)
Background: Posttraumatic disorders are among the most frequent co-occurring diagnoses in patients with substance use disorders (SUD). Individuals with this dual diagnosis often present with special treatment needs, especially after childhood traumatic experiences (CT). Along with posttraumatic stress disorder (PTSD) and dissociative symptoms, suicidal behaviors belong to the clinical challenges in this group of patients and may influence the course and outcome of SUD treatment. Therefore, a better understanding of the relationships between different forms of CT, psychopathology and suicidal behaviors seems to be important to tailor adequate concepts of care. Materials and Methods: We examined 343 female patients with SUD and Posttraumatic stress disorder (PTSD). All patients completed the Childhood Trauma Questionnaire (CTQ), the Dissociative Experiences Scale-Taxon (DES-T) and the Structured Clinical Interview Axis I Disorders (SCID-I). To determine relationships between different symptoms with potential importance for concepts of treatment, we conducted analyses of moderated mediation for different models. We examined the direct and indirect effects of associations between the type of CT, dissociation and suicidal behavior, as well as the moderation effect of PTSD. Results: All participants met DSM-criteria for either full PTSD (75.2%) or subsyndromal PTSD (24.8%). Almost all (94.5%) received at least one substance dependence diagnosis and the remaining 5.5% met substance abuse criteria. Most participants (93.3%) reported at least one type of childhood trauma. In all models, dissociation was a risk factor for suicidal ideation (SI) and for suicide attempts (SA). In both, participants with subsyndromal PTSD and participants with full PTSD, dissociation mediated the relationship between childhood sexual abuse and SI as well as SA. Moreover, we report direct effects between different childhood traumas and SI and SA. Furthermore, emotional abuse was a significant predictor of dissociation. Discussion: In our sample of female patients with SUD and co-occurring PTSD, dissociation significantly increased suicidal behavior and served as a mediator of the relationship between childhood sexual abuse and suicidal behavior. Our findings underline the need to include interventions to address dissociative symptoms and other more complex consequences of childhood trauma into concepts of care for patients with SUD.